2021
DOI: 10.1111/jmwh.13213
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Blood Pressure in Women in the United States: A Systematic Review

Abstract: Introduction Elevated blood pressure is a leading contributor to adverse cardiovascular outcomes. Some studies suggest there is an association between adverse childhood experiences (ACEs) and subsequent elevated blood pressure in adulthood. The literature specific to ACEs and blood pressure in women has not been synthesized; thus the purpose of this systematic review was to examine what is known about the association between ACEs and blood pressure in women living in the United States. Methods In collaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…As most research on trauma and CVH in Latinas has focused on childhood abuse, our findings contribute to a limited body of literature on the associations of exposure to trauma across the life course with CVH in this population. Moreover, investigators have previously found that lifetime trauma is associated with worse CVH in women (Mason et al, 2012(Mason et al, , 2013Rich-Edwards et al, 2012;Riley et al, 2010;Scott et al, 2021). However, few studies have investigated these associations in Latinas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As most research on trauma and CVH in Latinas has focused on childhood abuse, our findings contribute to a limited body of literature on the associations of exposure to trauma across the life course with CVH in this population. Moreover, investigators have previously found that lifetime trauma is associated with worse CVH in women (Mason et al, 2012(Mason et al, , 2013Rich-Edwards et al, 2012;Riley et al, 2010;Scott et al, 2021). However, few studies have investigated these associations in Latinas.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have examined lifetime trauma in relation to a comprehensive measure of CVH such as LS7. Furthermore, potentially traumatic experiences have been associated with poor CVH in women, but most research has had limited inclusion of racial and ethnic minority adults (Scott et al, 2021; Suglia et al, 2015, 2018). For instance, analyses of data from the Nurses’ Health Study II have found women who report childhood abuse or intimate partner violence are at higher risk of incident hypertension and diabetes (Mason et al, 2013; Riley et al, 2010).…”
mentioning
confidence: 99%
“…Fourth, as noted earlier, other exposures to traumatic stress (e.g. sexual abuse during childhood [37,52]) are associated with an increased cardiovascular risk, but we lacked data concerning those early exposures. Differentiating between cardiovascular risk that is associated with particular traumas, and sexspecific associations, is a focal area for future inquiry.…”
Section: Limitationsmentioning
confidence: 97%
“…6,7 There is growing evidence that childhood trauma is associated with increased risk for hypertension in adulthood. [8][9][10] For instance, a 2017 systematic review of 24 studies found that childhood trauma was positively associated with hypertension in 60% of included studies. 9 Furthermore, analyses of data from the Nurses' Health Study found that sexual and physical abuse prior to age 18 had a dose-dependent relationship with hypertension.…”
Section: Introductionmentioning
confidence: 99%